The Effect of Work Motivation and Job Involvement to Improve Organizational Commitment at Hasanuddin University Hospital, Indonesia - Nurintan Malik; Alimin Maidin; Andi Indahwaty Sidin; Irwandy Irwandy; Syahrir A Pasinringi; Syamsuddin Syamsuddin (ACHSM, 2024)
Background: Employees who have high work motivation and good job involvement can increase organizational employee commitment. This involves high levels of giving support, direction of goals, and involvement in optimizing themselves in carrying out tasks. This study aims to analyze the effect of work motivation and job involvement on nurse's organizational commitment at the Hasanuddin University Hospital, Makassar, Indonesia in 2022. Methods: Quantitative research has been completed using an observational study with a cross sectional study design. The sample used in this study involved 172 nurses at Hasanuddin University Hospital. The instrument used in this study was a questionnaire that has been tested for validity and reliability. Data analysis using Chi-Square test and Path Analysis was undertaken. Results: Study findings showed that there is an effect of work motivation on nurses' organizational commitment (p<0.001), work motivation on job involvement (p<0.001), job involvement on organizational commitment (p=0.003), and there is no effect of work motivation on organizational commitment through job involvement (p=0.051). Conclusion: Work motivation and job involvement directly affect the organizational commitment of nurses. It is recommended to the hospital to pay attention to work motivation and the involvement of nurses in their work in order to maintain commitment while developing direction and goals, hospital services, quality and future careers.